Effects of The Long-Time Wearing of Gloves by Health Care Workers Managing Covid-19 Assessed by Electrodermal Activity: A Pilot Study - Aldosky, Haval Y. Yacoob; Bari, Dindar S.; Martinsen, Ørjan Grøttem (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Continues wearing gloves is a crucial problem among health care workers treating patients with coronavirus (COVID-19) infection that may cause skin complications. In the present study, the skin conductance (SC), skin potential (SP) and skin susceptance (SS) were used to identify the effects of long-term wearing gloves among health care workers managing COVID-19. The experimental procedure was repeated 30 times on three subjects recruited as volunteers to wear gloves for 4 hours. The baseline of parameters SC, SP, and SS were recorded at normal conditions without wearing the glove at zero time (To). The parameters were again recorded in the cases of glove-wearing with and without zinc oxide ointment (ZnO) for the same period. Noticeable differences were found in each of SC, SP and SS for subjects who wore gloves when compared to the baseline for 4 h. Results also showed significant differences in each of SP and SS during the same period with applying ZnO comparing to wearing gloves without applying ZnO. The results show that skin hydration is significantly improved by using ZnO. However, changing gloves at least every four hours of continuous wearing is recommended.